Analisis Marketing Mix pada Pola Konsumsi Jamu di Bantul Yogyakarta - Muhammad Fariez Kurniawan; Abdul Samad (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
This study aims to determine the consumption behavior of the community of Bantul Regency based on the consumption frequency and to determine the effect of the marketing mix aspect on the consumption behavior of the community of Bantul Regency. This study used a cross-sectional descriptive design and analyzed using multiple linear regression. Data collection was carried out for four months from August to November 2020. The questionnaire consisted of four variables, product, price, promotion, and place variables, which accumulatively contains 10 question instruments. The sample from this study was 320 respondents who met the inclusion criteria. The majority of respondents answered very rarely consume jamu in Bantul Regency with details only once in more than a month. The marketing mix aspect affects the consumption behavior of the community of Bantul Regency. Aspects of product, price, and place have a positive influence on consumer behavior, while the aspects of promotion have a negative influence on the jamu consumption behavior of the community of Bantul Regency.